Transition, height and well-being - Alicia Adserà; Francesca Dalla Pozza; Sergei Guriev; Lukas Kleine-Rueschkamp; Elena Nikolova (Global Labor Organization (GLO), 2019)
Using newly available data, we re-evaluate the impact of transition from plan to market on objective and subjective well-being. We find clear evidence of the high social cost of early transition reforms: cohorts born around the start of transition are shorter than their older or younger peers. The difference in height suggests that the first years of reform were accompanied by major deprivation. We provide suggestive evidence on the importance of three mechanisms which partially explain these results: the decline of GDP per capita, the deterioration of healthcare systems, and food scarcity. On the bright side, we find that cohorts that experienced transition in their infancy are now better educated and more satisfied with their lives than their counterparts. Taken together, our results imply that the transition process has been a traumatic experience, but that its negative impact has largely been overcome.
Keywords: 330